Αvβ3-Isoform specific erbium complexes highly specific for bladder cancer imaging and photodynamic therapy. Issue 3 (14th December 2016) - Zhou, Yan; Chan, Chi-Fai; Kwong, Daniel W. J.; Law, Ga-Lai; Cobb, Steven; Wong, Wai-Kwok; Wong, Ka-Leung
Abstract : We have synthesized a bifunctional erbium–porphyrin tumor imaging and PDT agent (Er–R3 ) that is capable of killing bladder cancer cells via its selective binding to the integrin αv β3 isoform overexpressed on the cell membrane. Abstract : We have synthesized a bifunctional erbium–porphyrin tumor imaging and PDT agent (Er–R3 ) that is capable of killing bladder cancer cells via its selective binding to the integrin αv β3 isoform overexpressed on the cell membrane.